2019
DOI: 10.3390/su11051339
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Characteristics and Early Warning Analysis of Economic Polarization Evolution: A Case Study of Jiangsu Province in China

Abstract: Economic polarization is a special manifestation of economic disparity which intensifies the gap between the rich and the poor in a region and brings about a series of social problems. Though more and more scholars are studying the phenomenon of economic polarization, there are few studies on polarization level division and early warning analysis in the existing literature. The main purpose of this paper is to propose a standard for rationally dividing the level of economic polarization. This paper firstly ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Второй является теория мультиполяризации, в нее входят центрально-периферическая и кластерная теории, теория развития сетей. Эти теории утверждают, что экономическая поляризация происходит не только в одном направлении, но и возможно одновременное развитие в направлении высокого класса и низкого уровня, образуя этим многополярные явления [Zou et al, 2019].…”
Section: методы исследования обоснование выбора исследования [Methods Rationale For the Choice Of Study]unclassified
See 1 more Smart Citation
“…Второй является теория мультиполяризации, в нее входят центрально-периферическая и кластерная теории, теория развития сетей. Эти теории утверждают, что экономическая поляризация происходит не только в одном направлении, но и возможно одновременное развитие в направлении высокого класса и низкого уровня, образуя этим многополярные явления [Zou et al, 2019].…”
Section: методы исследования обоснование выбора исследования [Methods Rationale For the Choice Of Study]unclassified
“…• регионы с низким уровнем поляризации, провинциальные районы, имеющие слабую связь с городами [Zou et al, 2019].…”
Section: методы исследования обоснование выбора исследования [Methods Rationale For the Choice Of Study]unclassified
“…Its population and land area account for 37.7% and 51.8% of Jiangsu Province. The level of economic and social development in Jiangsu Province shows the regional differences between Southern Jiangsu, Central Jiangsu, and Northern Jiangsu [6]. Affected by natural conditions and human factors, the development of northern Jiangsu lags behind that of southern and central Jiangsu, which is considered an economic "depression".…”
Section: Measurement Of Cultural Modernization Levelmentioning
confidence: 99%
“…Other scholars study the spatial polarization of Japanese land price evolution and Ukrainian public opinion polls with the help of the spatial variation function model, micro-dynamic model, and exploratory spatial analysis [ 42 , 43 ]. Additionally, some scholars measure and explore the level of spatial polarization in the development of urbanization, railway transportation, and scientific and technological innovation, and have found that the regional labor market, economic structure, settlement structure, population density, transportation infrastructure, etc., all affect the development of regional imbalances from different aspects [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%